The Impact of Leaders’ Collegiality on Teachers’ Engagement for Organizational Improvement: A Case Study in an IB School in the United Arab Emirates - AKIJIAN, ROUPINA (2023)
The essence of this study arises from the developments observed in the 21st century, where researchers have dedicated substantial endeavors towards investigating the importance of collegiate leadership in elevating the standard of education within school environments. This study delves into the crucial role of leaders' collegiality in driving school improvement, emphasizing the necessity for positive school leadership practices in enhancing educational quality. The primary objective is to investigate how leaders' collegiality contributes to school improvement and students' academic achievement. Shedding the light on the main research question, which is: What is the impact of leaders’ collegiality on teachers’ engagement for school improvement in IB schools? Drawing upon a range of leadership theories and studies, with particular emphasis on selected key theories, the research employs a mixed-methods approach, combining qualitative data from interviews with senior and middle leaders and teachers with quantitative data from surveys distributed to middle and senior leaders and teachers. This study does not only highlight the importance of leaders’ collegiality in Abu Dhabi schools but also ensures the importance of collegiality in IB schools since ADEC / ADEK evaluation forms as Irtiqaa that are utilized to evaluate schools’ performance in Abu Dhabi is one of the main aspects schools focus on in teachers’ performances to achieve during all school academic year. The findings of this study reveal that leaders' collegiality positively influences employees, fostering a conducive working environment and ultimately leading to improved student academic success. This study underscores the critical importance of leaders' collegiality in educational practice, offering insights for future research and emphasizing the need for positive school leadership practices in school improvement efforts.